Respostas
respondido por:
3
y = ax + b
qdo y = 0 ; x =0 0 = a.0 + b b= 0
qdo y =5 ; x = -1 5 = a (-1) + 0 a = -5
equação : y = - 5x
qdo y = 0 ; x =0 0 = a.0 + b b= 0
qdo y =5 ; x = -1 5 = a (-1) + 0 a = -5
equação : y = - 5x
respondido por:
3
(0,0) P(-1,5)
m= y-yo / x - xo
m= 5-0 / -1 - 0
m= -5
y-yo= m (x-xo)
y-0= -5(x - 0)
y -0= -5x
5x + y= 0
m= y-yo / x - xo
m= 5-0 / -1 - 0
m= -5
y-yo= m (x-xo)
y-0= -5(x - 0)
y -0= -5x
5x + y= 0
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás